Contrasting patterns of cytokinins between years in senescing aspen leaves - Edlund, Erik; Novak, Ondrej; Karady, Michal; Ljung, Karin; Jansson, Stefan (Plant, cell & environment, 2017)
Cytokinins are plant hormones that typically block or delay leaf senescence. We profiled 34 different cytokinins/cytokinin metabolites (including precursors, conjugates and degradation products) in leaves of a free-growing mature aspen (Populus tremula) before and after the initiation of autumnal senescence over three consecutive years. The levels and profiles of individual cytokinin species, or classes/groups, varied greatly between years, despite the fact that the onset of autumn senescence was at the same time each year, and senescence was not associated with depletion of either active or total cytokinin levels. Levels of aromatic cytokinins (topolins) were low and changed little over the autumn period. Diurnal variations and weather-dependent variations in cytokinin content were relatively limited. We also followed the expression patterns of all aspen genes implicated as having roles in cytokinin metabolism or signalling, but neither the pattern of regulation of any group of genes nor the expression of any particular gene supported the notion that decreased cytokinin signalling could explain the onset of senescence. Based on the results from this tree, we therefore suggest that cytokinin depletion is unlikely to explain the onset of autumn leaf senescence in aspen.
Keywords: chlorofyl; gene expression; Seasons; glukosidy; listy rostlin; autumn senescence; Weather; stanovení celkové genové exprese; metabolism; down regulace; počasí; Populus tremula; Genes, Plant; Plant Leaves; roční období; Populus; Biosynthetic Pathways; Glucosides; biosyntetické dráhy; Cytokinins; rostlinné geny; Down-Regulation; cytokininy; Gene Expression Profiling; Gene Expression Regulation, Plant; profiling; regulace genové exprese u rostlin; Chlorophyll